Evolution of the Upper São Francisco River Basin Determined by Morphotectonic Analyses, Minas Gerais, Brasil - DOI 10.5216/bgg.v19i1.15308 - Borges de Campos, Alfredo (Boletim Goiano de Geografia, 2011)
.